2021
DOI: 10.1002/ange.202109965
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopy of the Main Protease of SARS‐CoV‐2 and Fragment‐Based Screening Identify Three Protein Hotspots and an Antiviral Fragment

Abstract: The main protease (3CLp) of the SARS‐CoV‐2, the causative agent for the COVID‐19 pandemic, is one of the main targets for drug development. To be active, 3CLp relies on a complex interplay between dimerization, active site flexibility, and allosteric regulation. The deciphering of these mechanisms is a crucial step to enable the search for inhibitors. In this context, using NMR spectroscopy, we studied the conformation of dimeric 3CLp from the SARS‐CoV‐2 and monitored ligand binding, based on NMR signal assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…The ongoing COVID‐19 pandemic has created a serious threat to human health and life safety worldwide, thus, there is an urgent medical need to find more effective therapeutic strategies for combating COVID‐19 300–303 . Among all validated targets for fighting CoVs, including SARS‐CoV‐2, the highly conserved 3D structure of 3CL pro plays an essential role in CoV replication, and no known human protease possesses a similar cleavage specificity, making 3CL pro an ideal target for developing clinically effective anti‐SARS‐CoV‐2 agents 21,60,109,304,305 . It is worth noting that a wide range of compounds have been found to have strong to moderate SARS‐CoV‐2 3CL pro inhibitory effects in the past few years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing COVID‐19 pandemic has created a serious threat to human health and life safety worldwide, thus, there is an urgent medical need to find more effective therapeutic strategies for combating COVID‐19 300–303 . Among all validated targets for fighting CoVs, including SARS‐CoV‐2, the highly conserved 3D structure of 3CL pro plays an essential role in CoV replication, and no known human protease possesses a similar cleavage specificity, making 3CL pro an ideal target for developing clinically effective anti‐SARS‐CoV‐2 agents 21,60,109,304,305 . It is worth noting that a wide range of compounds have been found to have strong to moderate SARS‐CoV‐2 3CL pro inhibitory effects in the past few years.…”
Section: Discussionmentioning
confidence: 99%
“…[300][301][302][303] Among all validated targets for fighting CoVs, including SARS-CoV-2, the highly conserved 3D structure of 3CL pro plays an essential role in CoV replication, and no known human protease possesses a similar cleavage specificity, making 3CL pro an ideal target for developing clinically effective anti-SARS-CoV-2 agents. 21,60,109,304,305 It is worth noting that a wide range of compounds have been found to have strong to moderate SARS-CoV-2 3CL pro inhibitory effects in the past few years. To better understand the structural features of SARS-CoV-2 3CL pro inhibitors and their inhibitory mechanisms, this study systematically summarized the reported structurally diverse SARS-CoV-2 3CL pro inhibitors (including marketed drugs and other synthetic compounds, herbal constituents, and their derivatives), as well as their inhibition potentials and mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…To gain further insights into the performance of REMD simulations, we compared NMR chemical shift values for C α and H α atoms of M pro with the experimental data ( Cantrelle et al, 2021 ) ( Fig. 6 ) in water since co-solvents impact the predicted secondary structure and chemical shift values.…”
Section: Resultsmentioning
confidence: 99%
“…In several recent studies, the researchers attempted to unclose potential allosteric sites of MPro dimer by using different computational and experimental approaches [57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Here, we will discuss the results of this study considering those previous literatures.…”
Section: Transfer Entropy Analysis (Te)mentioning
confidence: 88%
“…It was shown that these molecules reduced viral RNA (vRNA) replication by at least two orders of magnitude in Vero E6 cells. By using NMR spectroscopy, a fragment-based screening was performed that led to the identification of 38 fragment hits 68 . Besides the substrate-binding pocket, one allosteric site was determined at the dimer interface of the MPro, based on a combined analysis of chemical shift perturbations (CSP) and the signal intensity changes upon fragment binding.…”
Section: Transfer Entropy Analysis (Te)mentioning
confidence: 99%